Safety run-in and part 1 of GIMEMA AML1718: venetoclax combined with FLAI as induction treatment in non–low-risk AML - Giovanni Marconi; Alfonso Piciocchi; Ernesta Audisio; Cristina Papayannidis; Marco Cerrano; Clara Minotti; Francesca Paoloni; Fabio Guolo; Monica Bocchia; Michela Rondoni; Albana Lico; Matteo G. Carrabba; et al. (Blood Advances)
Abstract: The standard induction treatment for acute myeloid leukemia (AML) has limited efficacy for patients with non–low-risk AML. We conducted a multicenter study phase 1b/2, Gruppo Italiano Malattie EMatologiche dell'Adulto AML1718, to investigate the safety and efficacy of venetoclax (VEN) combined with fludarabine, cytarabine, and idarubicin (V-FLAI) as an induction therapy for patients with non–low-risk AML aged <65 years and at intermediate or high European LeukemiaNet risk. After a safety run-in, patients were randomly allocated to VEN 400 mg or VEN 600 mg cohorts. The primary objectives were safety and composite complete remission (bone marrow blasts of <5% with any recovery). We report a predefined interim analysis after 57 patients. Median exposure to VEN during induction was 22 days. Effectiveness and safety were similar between VEN 400 mg and VEN 600 mg cohorts. The 60-day mortality rate was 5.8%. Prolonged aplasia was observed in patients receiving high doses of cytarabine during consolidation. Composite CR was achieved in 84% of patients. With a median follow-up of 20.6 months, 1-year overall survival was 71%, 1-year disease-free survival was 66.2%, and 1-year cumulative incidence of relapse was 24%. V-FLAI is an effective induction therapy for young and fit patients. Fifty-five more patients will be enrolled in part 2; they will receive VEN 400 mg + FLAI as predefined and will be evaluated centrally for measurable residual disease. This trial was registered at www.clinicaltrials.gov as #NCT03455504.